Equivalência de estímulos e generalização recombinativa no seguimento de instruções com pseudofrases (verboobjeto) - Postalli, Lidia Maria Marson (Universidade Federal de São Carlos, 2011)
An important issue in the field of verbal behavior is how a person understands and learns to behave according to verbal commands or instructions. The stimulus equivalence paradigm, as a model of symbolic behavior, may explain the origins of the comprehension of instructions. Following new instructions can result from the recombination of subunits of previously learned instructions. This work reports three studies that investigated questions related to instructional control. In the first two studies, the general objective was to establish pseudo-phrases (action-object) as members of equivalence classes with actions, objects and abstract pictures; and to verify whether, when employed with an instructional function, the pseudo-phrases and the abstract pictures would control the participants responding. Additionally, the studies asked whether participants would follow new (recombined) instructions. The third study investigated whether the overlapping of elements of pseudo-phrases in teaching phase would favor generalized instruction-following. In the studies 1 and 2, twelve of the thirteen participants learned the auditory-visual conditional discriminations among spoken pseudo-phrases and actions presented in videotapes and among the same sentences and abstract pictures. Probes for class formation showed that the same twelve children comprehended the sentences, relating, through equivalence, the pseudo-phrases, the actions and the abstract pictures. Similar performances were observed with the pictures, suggesting that they had been comprehended and that they could work as substitutes for (or equivalent to) oral instructions. However, none of the children followed new (recombined) instructions, although all children responded under partial control of what was previously taught (object or action). In Study 3, four participants learned auditory-visual conditional discriminations (Condition 1) among spoken pseudophrases and videotapes (each showing action-object) and followed oral instructions in the tests of the instructional control, but only one participant followed recombined sentences. Four other participants learned to follow the experimental instructions via execution of the action related to object in the simultaneous presence of the auditory stimulus and of the corresponding videotape (Condition 2), but did not present recombinative generalization. Seven of the eight participants followed new instructions in the pre-test of new training matrixes with overlapping of the elements of the sentences previously learned (that is, their responding was under the control of elements of the compound). As a whole, the results represent a systematic replication of previous results indicating that class formation could promote the comprehension of sentences and facilitate the instruction-following behavior when the sentences are used with instructional function. Regarding the development of stimulus control by subunits of these complex stimuli, the evidences were very fragile, but when it occurred, the recombination was clearly related to systematic training with overlapping of elements in different sentences, thus suggesting the relevance of this procedure as an effective teaching condition.
Stimulus equivalence and recombinative generalization of instructionfollowing with pseudo-phrases (action-object)
Keywords: Comportamento verbal; Controle de estímulos; Controle instrucional; Equivalência de estímulos; Generalização recombinativa; Cr; Stimulus control; Instructional control; Stimulus equivalence; Recombinative generalization; Action-object; Children; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL